CD73+CD8+ T cells define a subset with anti-tumor potential in DLBCL patients - Zhang, Lingyu; Cheng, Rui; Fan, Zongbing; Liu, Yunxiao; Huang, Jie; Peng, Jiabing (Frontiers in Medicine, 2025)
IntroductionCD73, a recently discovered immune checkpoint, catalyzes the conversion of AMP to adenosine, thereby suppressing anti-tumor immune responses.CD8+ T cells play a critical role in the immune response against cancer, yet their functionality can be modulated by various factors within the tumor microenvironment. In this study, we focus on identifying and characterizing CD73+CD8+ T cells in the peripheral blood of patients with diffuse large B-cell lymphoma (DLBCL), aiming to elucidate their functional and phenotypic roles in tumor immunity.MethodsUsing flow cytometry, we analyzed the expression of inhibitory receptors (e.g., PD-1, TIM-3) and activating markers (e.g., CD25, CD69) on CD73+CD8+ T cells compared to CD73−CD8+ T cells. In vitro functional assays were conducted to assess their cytotoxic activity against tumor cells, including cytokine production and tumor cell killing capacity.ResultsCD73+CD8+ T cells exhibited a distinct immunophenotypic profile, characterized by reduced expression of inhibitory receptors and enhanced cytotoxic activity compared to their CD73− counterparts. These cells demonstrated higher levels of effector molecules (e.g., IFN-γ, TNF-α) and lower exhausted markers. The findings suggest that CD73+CD8+ T cells may retain stronger anti-tumor potential.DiscussionThis study highlights CD73+CD8+ T cells as a unique functional subset with potential therapeutic relevance in DLBCL. Their reduced exhaustion and heightened cytotoxicity position them as promising targets for immunotherapy strategies. However, the dual role of CD73 in adenosine-mediated immunosuppression warrants further investigation to reconcile its pro-tumorigenic effects with the observed anti-tumor activity of CD73+CD8+ T cells. Our findings deepen the understanding of CD8+ T cell heterogeneity in DLBCL and emphasize the need for mechanistic studies to explore CD73’s context-dependent functions.